Optimization of Mechanical, Dynamical and Thermal Properties of a High Performance Tread Compound for Radial Tires - Mir Hamid Reza Ghoreishy; Ghasem Naderi; Ali Keshavarz (علوم و تکنولوژی پلیمر, 2013)
A high performance passenger tire tread compound was optimized for its mechanical, dynamical and thermal properties. A reference compound was based on a blend of SBR and BR, sulfur and other ingredients without accelerator, carbon black and aromatic oil. The effects of CBS/TMTD and TBBS/TMTD as accelerator systems were studied with different quantities and the best accelerator system was chosen. Then, the blends of N330 and N550 carbon blacks were added in different quantities and the properties of these samples were studied to determine the best carbon black blend. Finally, the effect of different quantities of aromatic oil was investigated and the optimized quantity of aromatic oil and the final properties of tire tread compound were defined. The mechanical and dynamical tests were carried out on appropriate samples to determine tensile strength, elongation-at-break, fatigue-to-failure, abrasion resistance, hardness, resilience, dynamical-mechanical properties and temperature rise due to the heat build-up. The results showed that the compound containing 0.8 phr CBS, 0.7 phr TMTD, 40 phr N330,20 phr N550 and 15 phr aromatic oils demonstrated the best properties.